The gender approach in formation of professional education: its relationship with remembrance - Josefa Caridad López-Ferrera; Nadia Barrabí-Guardiol (Maestro y Sociedad, 2016)
The article reveals the dialectical relationship of gender and socio-historical memory aims to reflect on the development of educational strategy in the formation of professional education from this perspective that enriches the educational professional culture of students, and its development through it; academic, research, labor and extension in acquiring skills, habits and values associated with the genre from inclusion, social justice and gender equality elements that enable viewed through the socio-economic roots gender asymmetries in what influences of historical memory, which places students at the center of the educational process, to be able to criticize, confront and resolve the problems in teaching practice, creatively and responsibly and meet the university social custom.